Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1007/s10681-023-03188-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of durum with ancient tetraploid wheats from an agronomical, chemical, nutritional, and genetic standpoints: a review

Abstract: Under intense breeding, modern wheats, such as durum (Triticum turgidum L. ssp. durum), are believed to have lost nutritional quality and protein content while increasing productivity. Emmer (Triticum turgidum ssp. dicoccum Thell) and wild emmer (Triticum turgidum ssp. dicoccoides) are alternative resources for breeding programs by offering favorable alleles to be introgressed into modern materials and thus broadening their genetic diversity. Studies conducted so far have shown that durum wheat has better perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…On the basis of the growing interest of consumers in wheats present before the Green Revolution, collectively named “ancient wheats,” parallel research is increasing to analyze them more in detail both from the nutritional and technological points of view ( Cabas-Lühmann et al., 2023 ; Roumia et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the growing interest of consumers in wheats present before the Green Revolution, collectively named “ancient wheats,” parallel research is increasing to analyze them more in detail both from the nutritional and technological points of view ( Cabas-Lühmann et al., 2023 ; Roumia et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…17,19 Triticum monococcum had an elevated GPC, 48,49 but, for T. durum, T. dicoccon and T. dicoccoides, the measured GPC was in the range of values reported in the literature. [49][50][51] In general, wild wheats and landraces are known to have higher GPC. 15,[50][51] One T. urartu genotype showed 28% protein content.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] In general, wild wheats and landraces are known to have higher GPC. 15,[50][51] One T. urartu genotype showed 28% protein content. 52 The five T. urartu genotypes analyzed in the present study showed lower GPC (192-229 g kg −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…These parameters include yield and related traits ( Maccaferri et al., 2019 ; Arriagada et al., 2020 ; Gupta et al., 2020 ), protein content ( Saini et al., 2022c ), mineral content ( Fatiukha et al., 2020 ), abiotic-related traits ( Bhusal et al., 2018 ), and biotic-related traits such as FHB ( Zhang et al., 2022 ). Nevertheless, research indicates that intensive breeding practices in modern wheats have led to increased productivity at the expense of diminished nutritional value, protein content, and resistance or tolerance to abiotic and biotic stressors ( Cakmak et al., 2010 ; Peng et al., 2011 ; Cabas-Lühmann et al., 2023 ). Various QTL studies were conducted, showing the substantial nutritive value and stress tolerance conferred by wild emmer.…”
Section: Discussionmentioning
confidence: 99%
“…These studies primarily aimed to identify alleles or markers associated with nutritional value, particularly concerning iron and zinc content ( Peleg et al., 2009a ; Liu et al., 2021 ), protein content ( Fatiukha et al., 2019 ), and tolerance or resistance to abiotic ( Peleg et al., 2005 ) and biotic stressors ( Huang et al., 2016 ). Some of these QTLs have been used in wheat breeding programs to enhance the genotypes by introducing alleles that broaden their genetic diversity, thereby improving nutritional content, protein content, and resistance or tolerance to stressors ( Kumar et al., 2018 ; Fatiukha et al., 2019 ; Kuznetsova et al., 2019 ; Cabas-Lühmann et al., 2023 ). However, despite all these studies on QTLs, wheat breeding programs have used only a limited subset of those genetic resources ( Cobb et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%